Data Transmission with Reduced Delay for Distributed Acoustic Sensors. (10th November 2015) - Ryu, Hyun-Gyu; Lee, Sang-Keum; Har, Dongsoo
This paper proposes a channel access control scheme fit to dense acoustic sensor nodes in a sensor network, where multiple acoustic sensor nodes within communication range of a cluster head are grouped into clusters. Acoustic sensor nodes in a cluster detect acoustic signals and convert them into electric signals (packets). Detection by acoustic sensors can be executed periodically or randomly. As a result, each acoustic sensor generates its packets (50 bytes each) periodically or randomly over short time intervals (400 ms~4 seconds) and transmits directly to a cluster head (coordinator node). Our approach proposes using a slotted carrier sense multiple access. All acoustic sensor nodes in a cluster are allocated to time slots and the number of allocated sensor nodes to each time slot is uniform. All sensor nodes allocated to a time slot listen for packet transmission from the beginning of the time slot for a duration proportional to their priority. The order of packet transmissions with the acoustic sensor nodes in the time slot is autonomously adjusted according to the history of packet transmissions in the time slot. In simulations, performances of the proposed scheme are demonstrated by the comparisons with other low rate wireless channel access schemes.